Respuesta :
Answer:
StepTo find the sum of the first Sn terms of a geometric sequence use the formula
Sn=a1(1−rn)1−r,r≠1,
where n is the number of terms, a1 is the first term and r-by-step explanation:
Answer: 745
Step-by-step explanation:
[tex]The\ sequence\ is\ a\ geometric\ one.u_1=75\\u_2=90\\u_3=108\\u_4=129.6\\u_5=155.52\\u_6=186.624\\\\common\ factor\ is\ 1.2=\frac{6}{5} \\\\Sum=u_1+u_2+...+u_6=\displaystyle \sum_{i=1}^{6} 75*(\frac{6}{5})^{i-1} \\=75*\dfrac{(\frac{6}{5}) ^6-1 }{\frac{6}{5}-1 }\\\\\\=75*\dfrac{1,985984}{\frac{1}{5} } \\\\=75*9,92992\\\\=744,744\\\\\approx{745}[/tex]